Programs supporting incarcerated and previously incarcerated indigenous peoples: a scoping review protocol - Aisha Faruqui; Gabriel B. Tjong; Helana Marie Boutros; Sterling Stutz; Angela Mashford-Pringle (International Journal of Circumpolar Health, 2024)
The overincarceration of Indigenous peoples and its impacts on individual and community health is a growing concern across Canada and the United States. Federally run Healing Lodges in Canada are an example of support services for incarcerated and previously incarcerated Indigenous peoples to reintegrate into community and support their healing journey. However, there is a need to synthesise research which investigates these programmes. We report a protocol for a scoping review that is guided by the following research question: What is known about culturally informed programmes and services available to incarcerated and previously incarcerated Indigenous peoples in Canada and the US? This scoping review will follow guidelines published by the Joanna Briggs Institute and the Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for scoping reviews. This review will only identify programmes that are guided by Indigenous ways of being and knowing in order to best serve Indigenous communities and our community partners. The results of this review will support the development of programmes that are necessary for understanding and addressing the diverse needs of incarcerated and previously incarcerated Indigenous peoples.